One last kill - Dugoni, Robert (Dugoni, Robert. Tracy Crosswhite series, 2023)
"Tracy Crosswhite is reopening the investigation into Seattle's Route 99 serial killer. After thirteen victims, he stopped hunting and the trail went cold, stirring public outrage. Now, nearly three decades after his first kill, Tracy is expected to finally bring closure to the victims' families and redeem the Seattle PD's reputation. Even if it means working with her nemesis, Captain Johnny Nolasco. Lead detective of the original task force, Nolasco dares Tracy to do what he failed to: close the case. Forming an uneasy alliance, Tracy and Nolasco revisit old leads and pursue new evidence only to unearth high-level corruption and cover-ups as dangerous as the elusive killer himself. At the risk of being exposed, such deadly and powerful forces will go to extremes to stay in the shadows. That's just where Tracy and Nolasco are headed--to find the twisted truth behind a killer's motives, his disappearance, and his chilling comeback" --